169k views
2 votes
Rewrite the given expression in the form 3^u where u is a constant or an algebraic expression.

(5√3)^x

Rewrite the expression in the form 2^u where u is an algebraic expression

(1/2)^x-3

Rewrite the expression in the form 2 Superscript u where u is an algebraic expression

9/3√3

Rewrite the expression in the form 2 Superscript u where u is an algebraic expression

16/3√2^x

1 Answer

6 votes

Solution: (1) The expression
(5√(3) )^x
\text{ is written as }
5^x3^{(x)/(2)
.


(5√(3) )^x=5^x(√(3) )^x\\(5√(3) )^x=5^x(3^(1)/(2) )^x\\(5√(3) )^x=5^x3^(x)/(2)

The value of u is
(x)/(2).

(2) The expression
((1)/(2))^x-3 is written as
2^(-x)-3
.


((1)/(2))^x-3=(2^(-1))^x-3\\((1)/(2))^x-3=2^(-x)-3

The value of u is -x.

(3) The expression
(9)/(3√(3) ) is written as
√(3) (2^0).


(9)/(3√(3) )=(9)/(3√(3) )((√(3))/(√(3)) )\\(9)/(3√(3) )=(9(√(3)) )/(3(3) )\\(9)/(3√(3) )=√(3) \\(9)/(3√(3) )=√(3)(2^0)

THe value of u is 0.

(4)The expression
\frac{16}{3(\sqrt{2^(x)} )} is written as
(1)/(3)(2^{4-(x)/(2)}).


\frac{16}{3(\sqrt{2^(x)} )}=(2^4)/(3(2^x)^(1/2))\\\frac{16}{3(\sqrt{2^(x)} )}=(1)/(3)(2^{4-(x)/(2)})

The value of u is
4-(x)/(2).

User StillFantasy
by
6.5k points